The Significance of Domestic Financing for Economic Growth in the South East European Countries - Filipović, Sanja; Barjaktarović, Lidija; Konjikušić, Snežana (Industrija, 2016)
In the South Еast Europe countries, bank loans are common and the most important form of financing, due to still underdeveloped financial market. The banks in these countries gained a considerable amount of foreign funds and play a prominent role in the growth of local economy. Given that banks grant loans based on investments of foreign capital and domestic deposits, the aim of this paper is to determine the importance of domestic sources of financing for the economic growth in the period after the reduction of foreign investments. The survey was conducted on a sample of eight selected countries of South East Europe (Western Balkans along with three countries that became members of the European Union during 2007-2012 - Bulgaria, Croatia and Romania - SEE-8). The panel data model was applied, where the GDP growth rate was taken as the dependent variable, while the analyzed independent variables were growth rates of the following parameters: assets, loan capacity, the participation of loans in GDP, loan capacity of the population, deposit capacity, deposit of the population, participation of household deposits in total deposit liabilities. The research results indicate that the growth rate of assets, the growth rate of household deposits and the growth rate of retail deposits have a positive impact on economic growth, while the share of loans in GDP, the growth rate of loans to households and the growth rate of deposit capacity have a negative impact on economic growth in SEE-8.